1956
DOI: 10.1021/ja01590a076
|View full text |Cite
|
Sign up to set email alerts
|

A New Atp-Forming Reaction: The Reductive Deamination of Glycine

Abstract: Novobiocin appears to be the first recorded example of the natural occurrence of a carbamate ester of a sugar derivative.The authors gratefully acknowledge the contributions of Drs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1957
1957
2011
2011

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…29 Glycine oxidase also catalyzes deamination of glycine and other amino acids. 29,30 Mechanistic study of this enzymatic reaction by Molla et al showed its reversible nature. 30 Glycine is also utilized by many anaerobic bacteria, 31,32 conveying it in a reductive deamination, yielding acetic acid and ammonia.…”
Section: Introductionmentioning
confidence: 99%
“…29 Glycine oxidase also catalyzes deamination of glycine and other amino acids. 29,30 Mechanistic study of this enzymatic reaction by Molla et al showed its reversible nature. 30 Glycine is also utilized by many anaerobic bacteria, 31,32 conveying it in a reductive deamination, yielding acetic acid and ammonia.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, glycine-dependent ATP production could be observed during this reaction. Cell-free extracts of C. sticklandii showed a somewhat lower activity of the enzyme although the value was about 10-fold higher than those reported by Stadtman & Elliott (1956). This might be due to the more gentle storage conditions established by Barnard & Akhtar (1979) and also used by us.…”
Section: -4mentioning
confidence: 48%
“…The reaction catalysed by glycine reductase was discovered by Stadtman & Elliott (1956) while investigating the degradation of glycine and other amino acids in a Stickland reaction by C . sticklandii.…”
Section: Selenium-dependent Glycine Fermentation 1463 D I S C U S S Imentioning
confidence: 99%
“…Proline and glycine are reduced by the enzymes Dproline reductase and glycine reductase (Stadtman, 1956;Stadtman & Elliot, 1956;Tanaka & Stadtman, 1979;Set0 & Stadtman, 1976;Andreesen et al, 1989).…”
Section: Introductionmentioning
confidence: 99%